Abordagens psicolinguísticas na escrita de respostas discursivas com estudantes do 9º ano do ensino fundamental - Lima, Fernando Henrique Ribeiro [UNESP] (2025)
This doctoral thesis was developed within the scope of the Postgraduate Program in Education (PPGE) of the Faculty of Science and Technology of the São Paulo State University, registered in the research line “formative processes, teaching and learning”. The general objective of this thesis is to understand forms of pedagogical mediation in the work with writing as interaction, based on the teaching practices of the Written Response discursive genre with 9th grade Elementary School students in writing workshops. Based on this general objective, the specific objectives were proposed to (a) characterize elements of writing teaching in the proposed workshops and (b) record the aspects of the Discursive Response as a discursive genre through an intervention proposal. The problem is that applied research only considers the theoretical aspects involving the work with responses aimed at the context of college entrance exam preparation or applies these aspects in response analysis situations, but does not create an interaction with the Elementary School classroom to record the aforementioned genre and its conditions of production and materialization. Based on this reality, the question that arises is configured as follows: how can we carry out the work with writing as interaction in writing workshops focused on the development of important knowledge for Elementary School? In this context, workshops were held with 9th grade students in a public school, using an activity book specially developed for this moment. In the workshops, the students interacted with the researcher and recorded a volume of written discursive responses in moments of diagnostic evaluation, development of learning in classroom interaction and, finally, procedural evaluation. Through the activity book, it was possible to develop a didactic-pedagogical mediation with activities proposed in order to lead the student to the appropriation of knowledge through the study of the Discursive Response genre. Through this research, we established the thesis that the Written Response discursive genre mediates between the systematized knowledge provided in school curricula and the training that students need to effectively function in society, indicating that memorizing structures of discursive genres is not enough, since what is relevant for teaching is to provide students with the opportunity to understand and position the writing of discursive responses in interactions marked by diverse language practices in society, a space in which statements are effectively constituted. The results of this research indicated that through the proposed mediations, the development of writing autonomy and the perception of writing as a social practice were fundamental elements manifested in the workshops that provided the consolidation of knowledge and important learning for 9th grade students in the transition phase to high school, enabling the consolidation of essential writing skills, such as the student's positioning at the time of writing. Finally, the study contributed to the continuity of the science of education by proposing a discussion focused on the classroom around the development of student learning through the mediation of the Portuguese Language teacher and the content worked on in the writing workshops, with a special focus on writing, autonomy and the constitution of the Discursive Response that organizes the discourse in the social practice in which they carry out their interactions with the most distinct purposes.